De Bosques Nacionales a Concesiones Forestales: estudio del Bosque Nacional Alexander von Humboldt desde una dimensión geohistórica (1960-2017) - Dunin Borkwski, Ana Sabogal (2022)
The article revised the history of the Bosque Nacional Alexander von Humboldt in 1965. Since the first forestry law in 1963. The usage model of forest resources on the peruvian Amazon has been in constant evolution due to diverse drivers at multiple scales, as for example the changes in the country’s economic model. As a long process of changes on national politics framework of forest management, there has been a loss of important referents. A distinct example of this was the first forestry law with its tool on forest management: Bosques Nacionales (National Forests). The motive behind this research is to make evidence of the evolution process on the national politics of Bosques Nacionales by the case study of the Bosque Nacional Alexander von Humboldt by assessing spatial, economic and social dynamic at multiples scales of the constantly changing territory. We aim to comprehend the direct relationship between migratory flows associated to the demand on economic activities in respect to land use. Deforestation is operationalized as the relationship of multiples impacts (legal framework, creation of road axes and demographic growth) which will be approached with an interdisciplinary methodology that allows quantifying these changes in forest cover and building a model of future deforestation of the forest by the use of geographic information systems.